Teenism – The Prejudice Against Adolescents. Issue 1 (31st December 2023) - Novick, Jack; Novick, Kerry Kelly
ABSTRACT: The authors build on Elisabeth Young-Bruehl's concept of "childism" to propose "teenism, " a prejudice against adolescents that has roots in generalization from pathology to normality in psychoanalytic theory, and has rippled into general cultural concepts of adolescence, to the detriment of clear diagnosis and creative generation of appropriate and effective techniques of adolescent treatment. Teenism leads to a lack of support and validation of teenagers' strengths and contributions to society, as well as undermining the importance of the role of parents in adolescent development and functioning.